Mapping of the podocin proximity-dependent proteome reveals novel components of the kidney podocyte foot process - Gerlach, Gary F.; Imseis, Zachary H.; Cooper, Shamus L.; Santos, Anabella N.; O’Brien, Lori L. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The unique architecture of glomerular podocytes is integral to kidney filtration. Interdigitating foot processes extend from the podocyte cell body, wrap around fenestrated capillaries, and form specialized junctional complexes termed slit diaphragms to create a molecular sieve. However, the full complement of proteins which maintain foot process integrity, and how this localized proteome changes with disease, remain to be elucidated. Methods: Proximity-dependent biotin identification (BioID) enables the identification of spatially localized proteomes. To this end, we developed a novel in vivo BioID knock-in mouse model. We utilized the slit diaphragm protein podocin (Nphs2) to create a podocin–BioID fusion. Podocin–BioID localizes to the slit diaphragm, and biotin injection leads to podocyte-specific protein biotinylation. We isolated the biotinylated proteins and performed mass spectrometry to identify proximal interactors. Results and Discussion: Gene ontology analysis of 54 proteins specifically enriched in our podocin–BioID sample revealed ‘cell junctions,’ ‘actin binding,’ and ‘cytoskeleton organization’ as top terms. Known foot process components were identified, and we further uncovered two novel proteins: the tricellular junctional protein Ildr2 and the CDC42 and N-WASP interactor Fnbp1l. We confirmed that Ildr2 and Fnbp1l are expressed by podocytes and partially colocalize with podocin. Finally, we investigated how this proteome changes with age and uncovered a significant increase in Ildr2. This was confirmed by immunofluorescence on human kidney samples and suggests altered junctional composition may preserve podocyte integrity. Together, these assays have led to new insights into podocyte biology and support the efficacy of utilizing BioID in vivo to interrogate spatially localized proteomes in health, aging, and disease.